Association of intraperitoneal ceftriaxone, intravenous gentamicin and oral metronidazole in the treatment of an abdominal abscess and peritonitis in a horse: Case report - Alonso, Juliana de Moura [UNESP]; Ávila, Alice Ribeiro [UNESP]; Apolonio, Emanuel Vitor Pereira [UNESP]; Dos Santos, Bruna [UNESP]; Alves, Ana Liz Garcia [UNESP]; Watanabe, Marcos Jun [UNESP]; Rodrigues, Celso Antônio [UNESP]; Hussni, Carlos Alberto [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2020)
Medical management of abdominal abscesses in horses requires prolonged antibiotic therapy and presents varied success rates. A 6-year-old male horse with a history of colic and multiple abdominal punctures to relieve gas was attended. At admission, tachycardia, tachypnea, hyperthermia, mucosal congestion, dehydration, and rigid gait were observed. The association of physical examination, laboratory and ultrasonographic findings allowed the diagnoses of peritonitis and abdominal abscess. Supporting treatment plus broad spectrum antibiotic therapy was performed: daily intraperitoneal ceftriaxone (25 mg/kg, 7 days); daily intravenous gentamicin (6.6 mg/kg, 7 days); per os metronidazole three times a day (15 mg/kg 12 days), followed by the same dose twice a day (15 mg/kg 33 days), totaling 45 days of treatment. Plasma fibrinogen and ultrasonographic examination were the most effective tools to evaluate abscess evolution. There was normalization of the physical examination 24 h after beginning the treatment, consecutive regression of the nucleated cell count in the peritoneal fluid, and regression of plasma fibrinogen and size of the abscess. On the 10th treatment day, the animal was discharged from the hospital, maintaining oral therapy with metronidazole every 12 h (15 mg / kg). When the animal returned on the 30th day, an abscess size regression was observed. However, there was no resolution, and therapy with metronidazole was maintained. On the 45th day of treatment, a new hospital evaluation was performed, where the abscess resolved, and metronidazole was suspended. It is highlighted that the therapeutic association used in the treatment of abdominal infection and abscess resulted in a rapid clinical response.
Associação da ceftriaxona intraperitoneal, gentamicina intravenosa e do metronidazol oral no tratamento de abscesso abdominal e peritonite em equino: Relato de um caso
Keywords: Abdominal infection; Fibrinogen; Horses; Intraperitoneal route; Sonography